Deriving structural information from experimentally measured data on biomolecules: a review - Smith, L; van Gunsteren, W; Allison, J; Daura, X; Dolenc, J; Hansen, N; Mark, A; Oostenbrink, C; Rusu, V (Wiley, 2016)
During the past half century, the number and accuracy of experimental techniques that can deliver values of observables for biomolecular systems have been steadily increasing. The conversion of a measured value Qexp of an observable quantity Q into structural information is, however, a task beset with theoretical and practical problems: (i) insufficient or inaccurate values of Qexp, (ii) inaccuracies in the function Q(~r) used to relate the quantity Q to structure ~r, (iii) how to account for the averaging inherent in the measurement of Qexp, (iv) how to handle the possible multiple-valuedness of the inverse ~r(Q) of the function Q(~r), to mention a few. These apply to a variety of observable quantities Q and measurement techniques such as X-ray and neutron diffraction, small-angle and wide-angle X-ray scattering, free-electron laser imaging, cryo-electron microscopy, nuclear magnetic resonance, electron paramagnetic resonance, infrared and Raman spectroscopy, circular dichroism, Förster resonance energy transfer, atomic force microscopy and ion-mobility mass spectrometry. The process of deriving structural information from measured data is reviewed with an eye to non-experts and newcomers in the field using examples from the literature of the effect of the various choices and approximations involved in the process. A list of choices to be avoided is provided.